Pemberdayaan Masyarakat dalam Pengelolaan Sampah Rumah Tangga Melalui Bank Sampah dan Pengendalian Vektor di Kelurahan Gung Negeri Kecamatan Kabanjahe Kabupaten Karo : Pengabdian - Restu Auliani; Riswanati Tanjung; Jernita Sinaga (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Waste is a major problem in Indonesia, including in Gung Negeri Village, Karo Regency. People still litter, do not sort their waste, and are not yet aware of the benefits of waste banks. The purpose of this community service is to improve the quality of environmental cleanliness in Gung Negeri Village in the areas of waste management and vector control, calculating density figures, increasing knowledge and skills about waste management, and making compost using the Berkeley method. This community service activity was carried out using several methods: namely Education: Training, and Mentoring. The activity was carried out in the Partner Village of Gung Negeri Village involving 50 participants from the community, neighborhood heads, and mosquito larvae cadres. The Density Figure value in Gung Negeri Village, Kabanjahe, Karo Regency is 4.3. This means the Yellow Area, so preventive efforts to prevent the development of Dengue Fever are carried out through Fogging activities. Community knowledge and skills have increased by 80% in waste sorting efforts. The community has been able to process organic waste using the Berkeley method and produce compost. The tonnage of waste received at the Waste Bank increased because savings from the community increased to 59.2 kg during the community service period.